Changing dentists' carious tissue removal behavior: Qualitative study and behavioral change simulation experiment. (February 2019) - Jeggle, L.-M.; Baker, S.R.; Schwendicke, F.
Abstract: Objectives: We aimed to understand why German dentists remain reluctant about selective carious tissue removal (SE), and to develop and test two interventions for changing dentists' behavior. Methods: Ten one-to-one interviews with German dentists were conducted, and identified themes linked to the Behavioral Change Wheel to develop two interventions. The intervention "Guideline" summarized a scientific statement on SE, while the intervention "Tool" simulated dentists having a removal tool (self-limiting handpiece) allowing them to reliably perform SE. For testing these interventions, a postal behavioral-change simulation-experiment was performed on German dentists (n = 1226/intervention), delivered via sealed envelopes. Dentists were first, without knowledge of the intervention, asked to fill out a questionnaire, including a question on their simulated removal behavior in deep lesions in vital teeth, measured via the dentin hardness dentists would leave close to the pulp. After opening the sealed envelope and receiving the simulated intervention, dentists filled out a second identical questionnaire. Results: Based on identified barriers (lack of guidelines, discrepancy between established and "new" knowledge, lack of routine) and facilitators (understanding the biological foundations for SE, knowing it was evidence-based, having reliable criteria for determining the endpoint of SE), the two interventions were developed. 504 dentists participated in the experiment (response rate:24.9%). For both interventions, the outcome behavior improved significantly after the intervention (p < 0.001), with 29.6% (guideline) and 17.9% (tool) changing their behavior towards SE, respectively. There were no significant differences in the outcome behavior between the two interventions (p = 0.933). Conclusion: Systematically developed behavior-change interventions may be efficacious to improve the uptake of SE. Clinical significance: Understanding the barriers and facilitators for applying SE facilitates the development of interventions which may be efficacious for changing carious tissue removal.